The Effect of Animated Videos on Teeth Brushing on School Children's Knowledge of Maintaining Dental and Oral Health” - St. Nurfatul Jannah; Rismanudin Rismanudin; Yosephina Yunita Ongirwalu (GLOBAL HEALTH SCIENCE GROUP, 2025)
Dental caries remains a common health problem among children in many countries, including Indonesia, with a fairly high incidence rate. According to data from Riskesdas (2018), 81.5% of children aged 3-4 years in Indonesia suffer from dental caries. Lack of knowledge and poor oral hygiene practices can increase the risk of dental health problems. Educational media in the form of animated videos are considered effective because they stimulate visual and auditory senses, thereby aiding children's understanding. This study aims to evaluate the effect of an animated video on proper toothbrushing techniques on students' knowledge levels at SDN Bontoramba 1 Makassar. It is hoped that the implementation of such media can enhance children's awareness and knowledge about oral and dental care, thereby positively impacting their quality of life. This study aims to determine children's level of knowledge about dental and oral health care before receiving education through animated videos, then analyze changes in knowledge after the education, and assess the effect of animated videos on children's motivation to maintain dental and oral health. The research used a quasi-experimental design with a pre-post test approach, This study involved 36 elementary school students, consisting of 16 girls and 20 boys. The respondents were assessed before watching the educational animation video and then reassessed after the educational intervention through the video. Based on the McNemar test analysis, 29 students who initially had poor knowledge improved to good after watching the animated educational videos, and no students showed a decline from good to poor. The statistical test results showed a significance value of p < 0.001, which is less than the criterion limit of 0.05 There was a significant difference between the results before and after the intervention. These findings indicate that the use of animated educational videos has a significant effect on improving students' knowledge of how to brush their teeth to maintain dental and oral health.